2020
DOI: 10.3390/jof6040191
|View full text |Cite
|
Sign up to set email alerts
|

The High Osmolarity Glycerol (HOG) Pathway Functions in Osmosensing, Trap Morphogenesis and Conidiation of the Nematode-Trapping Fungus Arthrobotrys oligospora

Abstract: Hog1, a mitogen-activated protein kinase (MAPK), has been identified in diverse fungal species, and it regulates various cellular processes, such as osmoadaptation, nutrient-sensing, and pathogenesis. However, the roles that Hog1 plays in nematode-trapping fungi were previously unclear. Here, we characterized orthologs of Saccharomyces cerevisiae Hog1 and membrane mucin Msb2 in the nematode-trapping fungus Arthrobotrys oligospora. We generated gene deletion mutants of HOG1 and MSB2 in A. oligospora, and charac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
36
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(36 citation statements)
references
References 42 publications
0
36
0
Order By: Relevance
“…Nematodes and fungi depend on and communicate through elaborate networks of signaling. The MAPK signaling cascades are key evolutionarily conserved signal transducers in all eukaryotes, and several MAPKs have been identified in A. oligospora , including Slt2 ( Zhen et al, 2018 ; Chen et al, 2021 ), Fus3 ( Chen et al, 2021 ), Hog1 ( Kuo et al, 2020 ), and Ime2 ( Xie et al, 2020 ). In filamentous ascomycetes, the Slt2-MAPK cascade pathway is an important signaling pathway, which consists of Bck1 , Mkk1/2 , and Slt2 in S. cerevisiae ( Levin, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…Nematodes and fungi depend on and communicate through elaborate networks of signaling. The MAPK signaling cascades are key evolutionarily conserved signal transducers in all eukaryotes, and several MAPKs have been identified in A. oligospora , including Slt2 ( Zhen et al, 2018 ; Chen et al, 2021 ), Fus3 ( Chen et al, 2021 ), Hog1 ( Kuo et al, 2020 ), and Ime2 ( Xie et al, 2020 ). In filamentous ascomycetes, the Slt2-MAPK cascade pathway is an important signaling pathway, which consists of Bck1 , Mkk1/2 , and Slt2 in S. cerevisiae ( Levin, 2005 ).…”
Section: Discussionmentioning
confidence: 99%
“…AoFlbA was significantly downregulated compared to 0 h (4.4-, 5.2-, and 8.2-fold at 12, 24, and 36 h, respectively), especially in the later infection stage (Figure 1c). Meanwhile, AoRgsA, AoRgsB, and AoRgsB2-2 were also downregulated at three time points (12,24, and 36 h). In contrast, AoRgsB2-3 and AoRgsC were significantly upregulated at 12, 24, and 36 h. Specifically, AoRgsB2-3 increased by 2.8-3.0 fold at 12, 24, and 36 h, respectively.…”
Section: Expression Of Seven Rgs-encoding Genes During Trap Formationmentioning
confidence: 92%
“…In our previous study, proteomic analysis of A. oligospora showed that multiple signal transduction pathways are involved in the regulation of trap formation [ 22 ]. Recently, several signaling proteins associated with G protein signaling, such as mitogen-activated protein kinases Slt2 [ 23 ], Hog1 [ 24 ], and Ime2 [ 25 ], calcium/calmodulin-dependent protein kinases [ 26 ], and Gβ [ 20 ], were proven to regulate trap formation and pathogenicity in A. oligospora . However, the functions of RGSs in A. oligospora and other NT Fungi are unknown.…”
Section: Introductionmentioning
confidence: 99%
“…Signal perception, transduction, and, consequently, the response to environmental changes is a prerequisite for fungal biology and controls essential pathways, such as stress response, differentiation processes, metabolism, and pathogenicity [ 1 ]. The high osmolarity glycerol (HOG) pathway consists of a multistep phosphorelay (MSP) system connected to a conserved mitogen-activated protein kinase (MAPK) cascade [ 2 ].…”
Section: Introductionmentioning
confidence: 99%